William of Sherwoods Treatise on Syncategorematic Words. - Kretzmann, Norman (University of Minnesota Press, 1968)
This is the first translation of an important medieval work in philosophy, an advanced treatise by the thirteenth-century English logician William of Sherwood. The treatise draws on doctrines developed in Sherwoods Introduction to Logic, which has also b.